COMMUNITY PARTICIPATION IN SUPPORTING WOMEN ACHIEVING REGIONAL LEADERSHIP - Sa’diyah El Adawiyah; Astriana Baiti Sinaga; Lusi Andriyani (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
Public participation is a hallmark of political modernization. There are two characters used to capture the informant's view of community participation, namely sociological and cultural conditions. Sociological conditions refer to the empirical and objective dimensions of the audience or community participation, which are all people belonging to the infrastructure and political superstructure—the purpose of this study: community participation in supporting women to achieve leadership. The method used in this research is a qualitative approach with case studies. The subjects of this study were three relatively prominent female regional heads, namely: female regional heads from dynastic typology, politician typology and bureaucratic typology. The three women regional heads are incumbent elements. The results of the women's research determine practical steps in realizing tolerance, identifying personal, mostly female regional heads who have a side of attractiveness and power which is carried out together, not to endure joint suffering but for mutual progress.